Porous carbon polyhedrons with exclusive Cu-Nx moieties as highly effective electrocatalysts for oxygen reduction reactions. (10th August 2021) - Liu, Yalin; Rao, Peng; Zhong, Mingjun; Li, Ruisong; Li, Jing; Du, Yanlian; Deng, Yijie; Shen, Yijun; Tian, Xinlong
Abstract: The design and development of robust and efficient non-Fe doped transition metal-nitrogen doped carbon (TM-N/C) catalysts for oxygen reduction reaction is significant for promoting the applications of TM-N/C based catalysts in sustainable energy devices such as metal-air batteries and fuel cells. In this study, exclusive Cu-Nx moieties implanted in metal-organic framework (MOF) polyhedrons are successfully fabricated by an adsorption-calcination approach. The optimal electrocatalyst (CuNC-1100) exhibits much higher stability and satisfactory catalytic activity with a half-wave potential (E1/2 ) of 0.885 V, which is 40 mV higher than commercial Pt/C in 0.1 M KOH solution, and exhibits a dominant 4-electron direct reaction path. The comprehensive characterization data reveals that the high activity of the catalyst originates from the porosity and high surface area, high dispersion of Cu atoms, and high density of graphitic nitrogen content and Cu-Nx species. Graphical abstract: Image 1 Highlights: Porous carbon polyhedrons catalyst is prepared by an adsorption-calcination approach. High density of Cu-Nx species and graphitic nitrogen efficiently catalyzed oxygen reduction reaction (ORR). The optimal CuNC-1100 catalyst exhibited an excellent ORR performance in 0.1 M KOH.